PENGARUH POWER TUNGKAI DAN FLEKSIBILITAS TERHADAP HASIL TENDANGAN MAWASHI GERI PELAJAR EKSTRAKURIKULER KARATE SMA NEGERI 2 KALIANDA - Rani Oktasari; Akor Sitepu; Frans Nurseto; Herman Tarigan (Journal Physical Education, Health and Recreation, 2018)
This study aims to determine the effect of leg power, and flexibility on the results of kick mawashi geri karate extracurricular students in State High School 2 Kalianda, South Lampung. Sanpel from this study amounted to 11 people consisting of 3 women and 8 men. Data is collected through power limb tests using standing broad jump, flexibility by using the sit and reach test, and mawashi geri kicks using the stopwatch. The results showed that the leg power had a value of t - 2,459, for α 5% with dk = n-1 and flexibility had a value of t counted 4,152 with t table 2,228 for α 5% with dk = n-1. The conclusion of this study shows that there is a significant influence on the power of the legs against the results of the mawashi geri kick, and there is a significant effect of flexibility on the results of the mawashi geri kick.